2006
DOI: 10.1007/s00262-006-0274-z
|View full text |Cite
|
Sign up to set email alerts
|

The C-type lectin MGL expressed by dendritic cells detects glycan changes on MUC1 in colon carcinoma

Abstract: The epithelial mucin MUC1 is a high molecular weight membrane glycoprotein frequently overexpressed and aberrantly glycosylated in adenocarcinoma. Mucins normally contain high amounts of O-linked carbohydrate structures that may influence immune reactions to this antigen. During malignant transformation, certain glyco-epitopes of MUC1, such as Tn-antigen, TF-antigen and their sialylated forms become exposed. The role of these glycan structures in tumor biology is unknown, but their presence is known to correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 45 publications
1
114
0
1
Order By: Relevance
“…Tn expression is associated with poor prognosis, along with accelerated tumor progression and metastasis (1). Although the advantages for tumor cells carrying Tn antigen are not fully understood, binding of Tn antigen by a C-type lectin, termed MGL, on both dendritic cells and macrophages enhances tolerance to the tumor cells (34)(35)(36). Future studies using this animal model can explore whether Tn(+) cells or tissues become more susceptible to mutagenesis in the mosaic animals, and whether Tn(+) cells in vivo have survival and growth privileges.…”
Section: Discussionmentioning
confidence: 99%
“…Tn expression is associated with poor prognosis, along with accelerated tumor progression and metastasis (1). Although the advantages for tumor cells carrying Tn antigen are not fully understood, binding of Tn antigen by a C-type lectin, termed MGL, on both dendritic cells and macrophages enhances tolerance to the tumor cells (34)(35)(36). Future studies using this animal model can explore whether Tn(+) cells or tissues become more susceptible to mutagenesis in the mosaic animals, and whether Tn(+) cells in vivo have survival and growth privileges.…”
Section: Discussionmentioning
confidence: 99%
“…87 Although the diversity and signaling mediated by these receptors remains to be clarified, engagement of these receptors by tumor cells may have major effects on antigen presentation. Some examples of potential CLR ligands expressed by tumor cells include muc1, which binds to the mannose receptor and galactose-type clectin 88 and the carcinoembryonic antigen (CEA), which binds to DC-SIGN. 89 Role of TOLL-like receptors.…”
Section: Interaction Of Dcs With Dying Tumor Cellsmentioning
confidence: 99%
“…Moreover, in vivo, MGL appears to play a crucial role in close proximity of the endothelial structures of lymph nodes and thymus, where iDCs are hampered in their migration activity until maturation [6]. In cancer, MGL has been described to enable DCs to sense glycosylation [17] and to selectively recognize tumor-associated glycoproteins [18]. The Tn-MUC1 glycoform represents one of the tumor-associated antigens (TAAs) studied as an MGL ligand.…”
mentioning
confidence: 99%
“…The targeting of CLRs on DCs has recently acquired a great interest for cancer immunotherapy. Several authors have recently demonstrated that CLR targeting represents an optimal strategy to enhance antigen presentation by DCs, because CLRs are the designed receptors that can recognize endocytose glycans expressed by TAAs released during tumor progression [10,17,18]. Different approaches have been proposed to target CLRs in vivo and in vitro, such as antigen coupling to CLR-specific antibody and recombinant glycoproteins [28].…”
mentioning
confidence: 99%